HelperFriend, a Serious Game for Promoting Healthy Lifestyle Behaviors in Children: Design and Pilot Study - Ismael Edrein Espinosa-Curiel; Edgar Efrén Pozas-Bogarin; Maryleidi Hernández-Arvizu; Maria Elena Navarro-Jiménez; Edwin Emeth Delgado-Pérez; Juan Martínez-Miranda; Humberto Pérez-Espinosa (JMIR Publications, 2022)
BackgroundThe use of health games is a promising strategy for educating and promoting healthy lifestyle behaviors among children. ObjectiveWe aimed to describe the design and development of a serious game, called HelperFriend, and evaluate its feasibility, acceptability, and preliminary effects in children in a pilot study. HelperFriend is a vicarious experiential video game designed to promote 3 lifestyle behaviors among young children: physical activity, healthy eating, and socioemotional wellness. MethodsParticipants aged 8 to 11 years were recruited from an elementary school and randomized to receive a healthy lifestyle behavior educational talk (control) or play six 30-minute sessions with HelperFriend (intervention). Assessments were conducted at baseline (T0) and after the intervention (ie, 4 weeks) (T1). The primary outcome was gain in knowledge. The secondary outcomes were intention to conduct healthy behaviors, dietary intake, and player satisfaction. ResultsKnowledge scores of intervention group participants increased from T0 to T1 for physical activity (t14=2.01, P=.03), healthy eating (t14=3.14, P=.003), and socioemotional wellness (t14=2.75, P=.008). In addition, from T0 to T1, the intervention group improved their intention to perform physical activity (t14=2.82, P=.006), healthy eating (t14=3.44, P=.002), and socioemotional wellness (t14=2.65, P=.009); and there was a reduction in their intake of 13 unhealthy foods. HelperFriend was well received by intervention group. ConclusionsHelperFriend appears to be feasible and acceptable for young children. In addition, this game seems to be a viable tool to help improve the knowledge, the intention to conduct healthy behaviors, and the dietary intake of children; however, a well-powered randomized controlled trial is needed to prove the efficacy of HelperFriend.